Sabana 2050 (2017)
This projects is an installation based on the investigation about the economic, social and architectonic joint in historic periods of the Estación de la Sabana, the main train station in Bogotá. This project is also an analysis of its present decay state seen from a patrimonial administration perspective. The project generates a story of fictional future based on fundamental and relevant aspects of the investigation that speak about an administration that do not have into consideration the realities of the industry but instead are based in a colonialist speech of imported technological advances that respond just a to national reality. Those aspects are used in the design of a fiction scenario framework as an hibrid two of pre-existing models.